2012
DOI: 10.1007/s00246-012-0513-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Imaging Detects Impaired Biventricular Performance Shortly After Congenital Heart Defect Surgery

Abstract: Cardiac surgery with cardiopulmonary bypass is associated with the development of a systemic inflammatory response, which can lead to myocardial damage. However, knowledge concerning the time course of ventricular performance deterioration and restoration after correction of a congenital heart defect (CHD) in pediatric patients is sparse. Therefore, the authors perioperatively quantified left ventricular (LV) and right ventricular (RV) performance using echocardiography. Their study included 141 patients (ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
5
17
1
Order By: Relevance
“…
opinion, this is an excellent manuscript describing impaired systolic and diastolic biventricular performance shortly after congenital heart defect (CHD) surgery.The authors clearly state that only tissue Doppler parameters such as the tricuspid annular peak systolic velocity (S 0 ) and the M-mode parameter tricuspid annular plane systolic excursion (TAPSE) were able to detect impairment of systolic right ventricular (RV) function [1].We completely agree with their findings and may add that in our opinion, this impairment can persist up to 1 year postoperatively. We note also that after surgery for tetralogy of Fallot, these parameters worsen continuously over time in pediatric and adolescent patients [2,3].

The authors state that a need exists for a detailed evaluation of the RV function parameters (e.g., the S 0 in this pediatric population) [1].

…”
supporting
confidence: 73%
See 4 more Smart Citations
“…
opinion, this is an excellent manuscript describing impaired systolic and diastolic biventricular performance shortly after congenital heart defect (CHD) surgery.The authors clearly state that only tissue Doppler parameters such as the tricuspid annular peak systolic velocity (S 0 ) and the M-mode parameter tricuspid annular plane systolic excursion (TAPSE) were able to detect impairment of systolic right ventricular (RV) function [1].We completely agree with their findings and may add that in our opinion, this impairment can persist up to 1 year postoperatively. We note also that after surgery for tetralogy of Fallot, these parameters worsen continuously over time in pediatric and adolescent patients [2,3].

The authors state that a need exists for a detailed evaluation of the RV function parameters (e.g., the S 0 in this pediatric population) [1].

…”
supporting
confidence: 73%
“…We note also that after surgery for tetralogy of Fallot, these parameters worsen continuously over time in pediatric and adolescent patients [2,3].The authors state that a need exists for a detailed evaluation of the RV function parameters (e.g., the S 0 in this pediatric population) [1]. They found that S 0 was significantly lower in the surgically treated CHD patient group than in the control group.…”
mentioning
confidence: 85%
See 3 more Smart Citations